Control, Digital Signage, remote OPTIMIZATION OF CONTROL AND MONITORING ON DIGITAL SIGNAGE BASED ON REMOTE DESKTOP AT I GUSTI NGURAH RAI AIRPORT, BALI - PUTU, WIDI ARYANI; Sukarwoto, Sukarwoto (Jurnal Penelitian, 2024)
Digital signage has become one of the important communication tools in airport environments to provide information to passengers and visitors. However, to ensure that the displayed information remains relevant, up-to-date, and controlled, an effective system of control and monitoring is required. At I Gusti Ngurah Rai Bali Airport, this improvement can be achieved by adopting a remote desktop-based solution. This research aims to optimize the control and monitoring of digital signage at I Gusti Ngurah Rai Bali Airport through the use of a remote desktop-based system. The methods used include evaluating existing digital signage infrastructure, selecting appropriate remote desktop platforms, integrating with existing digital signage systems, setting access and authorization, training personnel, monitoring and maintaining the system regularly, and continuous evaluation and improvement. It is hoped that by implementing this solution, I Gusti Ngurah Rai Bali Airport can improve efficiency in information management, ensure the availability of accurate and timely information for passengers, and provide a better overall airport experience for users.